Analysis of the mechanism of renewable energy on energy-saving and environmental protection industry: Empirical evidence from four countries. (November 2022) - Wei, Qifeng; Guo, Anni; Wei, Lixia; Ni, Weiyi
Abstract: The "Carbon Peaking and Carbon Neutrality" strategy of China has accelerated the process of industrial structure transformation of global energy-saving and environmental protection. With the international efforts to cope with climate change and the growing consensus on low-carbon energy, many countries have introduced policy measures to promote the development of the renewable energy industry. This paper constructs an empirical model to analyze the mechanism of four kinds of renewable energy power generation technologies on energy consumption in four countries, and further discusses the impact of main renewable energy power generation technologies on the development of the smart environmental protection industry of China under the "Carbon Peaking and Carbon Neutrality" goal. The results show that there is a huge gap in renewable energy technologies among different countries. There is technical heterogeneity in the effects of four kinds of renewable energy technologies on energy consumption, which can effectively reduce energy consumption on the whole. Renewable energy technologies have an impact on the development of the smart environmental protection industry in China from different aspects, which is generally conducive to promoting the development of energy-saving and environmental protection emerging industry. Finally, combined with the empirical conclusions, this paper puts forward suggestions on how to effectively optimize the construction of energy-saving and environmental protection emerging industry in the development of renewable energy technologies.